Facial Plastic and Reconstructive Surgery - Adamson, Peter A.; Papel, Ira D.; Frodel, John L.; Holt, G. Richard; Larrabee Jr., Wayne F.; Nachlas, Nathan E.; Park, Stephen S.; Sykes, Jonathan M.; Toriumi, Dean M.; Ahn, Edward S.; Alam, Daniel S.; Ames, Julie A.; et al. (Thieme, 2016)
This fourth edition of Facial Plastic and Reconstructive Surgery keeps readers up-to-date on recent developments in the field, including microvascular techniques, minimally invasive cosmetic procedures, and unique applied technologies. Along with comprehensive surgical chapters, the text addresses practical issues driving changes in facial plastic surgery practice: ethnic variations, anti-aging strategies, ambulatory surgical concerns, and evidence-based decision making. Key Features: Online access to more than 30 videos demonstrating the latest procedures and techniques New chapters on African rhinoplasty, facial paralysis treatment, evidence-based facial plastic surgery, tissue engineering, costal rib utilization techniques, and face transplants Clinical insights from luminaries in the field of facial plastic and reconstructive surgery More than 2,000 full-color images and illustrations demonstrate main concepts For over two decades experienced surgeons, fellows, and residents have successfully relied on Facial Plastic and Reconstructive Surgery to prepare for surgery and clinical rotations, as well as their in-service and board exams. Today's facial plastic surgeons know this new edition offers them the latest, most comprehensive coverage of facial plastic surgery. Practicing facial plastic surgeons, plastic surgeons, and otolaryngologists will use this book to stay up-to-date on developments in the field and to brush up on less familiar procedures.
Keywords: Face : Surgery; Surgery, Plastic; Face : surgery; Cosmetic Techniques; Reconstructive Surgical Procedures